The Role of Quality Management in Ensuring the Accuracy of Clinical Laboratory Teest Result at Grandmed Lubuk Pakam Hospital - Siti Ramadhani; Ahmad Hafizullah Ritonga; Basyariah Lubis (JURNAL KESMAS DAN GIZI (JKG), 2026)
Clinical laboratories hold an important role in modern healthcare services because approximately 60–70% of medical decisions depend on laboratory examination results. Therefore, the accuracy of these results becomes a fundamental aspect that must be maintained through the implementation of comprehensive quality management. Laboratory quality is strongly influenced by three main phases, namely the pre-analytic, analytic, and post-analytic phases. Various studies show that most errors occur in the pre-analytic phase, such as incorrect patient identification, improper specimen collection, and unsuitable storage conditions. Thus, the ability of laboratory personnel to apply standard operating procedures (SOPs) becomes a crucial factor in efforts to improve result accuracy. This study aims to analyze the relationship between human resource competence, the implementation of Quality Assurance (QA), and Quality Control (QC) with the accuracy of laboratory examination results at Grandmed Lubuk Pakam Hospital. The research used a quantitative approach with a cross-sectional design and involved 30 laboratory personnel. Data were obtained through structured questionnaires and analyzed using the Spearman’s rho correlation test. The results showed a very strong relationship between human resource competence and examination accuracy (r = 0.938; p < 0.001), QA and accuracy (r = 1.000; p < 0.001), as well as QC and examination accuracy (r = 0.984; p < 0.001). These findings emphasize that good quality management—supported by competent laboratory personnel and consistent implementation of QA and QC—plays a major role in ensuring the accuracy of examination results. Regular quality evaluations are necessary to improve patient safety and support more accurate clinical decision-making.ongoing basis through improving laboratory personnel competence, ensuring consistent application of QA and QC at all stages of laboratory testing, and conducting regular quality evaluations to support patient safety and accurate clinical decision-making.